Reinforcement effects of multi-scale hybrid fiber on flexural and fracture behaviors of ultra-low-weight foamed cement-based composites. (April 2022) - Yang, Yuanyi; Zhou, Qi; Deng, Yi; Lin, Jinhui
Abstract: In this paper, the flexural behavior and fracture parameters of ultra-low-weight foamed cement-based composites (FCC) reinforced by a novel fiber hybridization containing short PP fiber, and CaCO3 whisker was investigated. The flexural behavior, fracture failure, fracture toughness, and fracture energy of FCC with multi-scale fibers have been comprehensively evaluated. The fiber hybridization performed better fracture performances than that of incorporation of mono PP fiber or CaCO3 whisker, which has provided a grading crack resistance in the ultra-low-weight FCC and achieved the synergistic reinforcing effect. Accordingly, this work is helpful towards the foundation of optimal design for fracture toughness analysis in fiber-reinforced lightweight cement elements.